Phytochemical Screening of Suji (Pleomele angustifolia) Extract - Bahri, Syamsul; Setiadi, Dadi; Lestari, Tri Ayu; Setiawan, Heru; Hakim, Muhammad Alfianul; Cahyadi, Lalu M. Zidan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Phytochemical screening of Suji (Pleomele angustifolia) extract has been conducted. The aim of this research is to identify compounds and determine the antioxidant activity of suji extract. The method used is laboratory experiments for phytochemical screening and antioxidant activity testing. This research consists of 2 (two) stages. The first stage aims to obtain extract of suji by using ethanol plus ethyl acetate and the second stage is carried out to test the content of secondary metabolite compounds using phytochemical tests and determine the antioxidant activity of extract of suji using the DPPH method. The extract of suji positively contains terpenoids, whereas flavonoid and alkaloids are detetcted in a significant number. The DPPH test results obtained the equation y = 0.3492x + 12,059, indicating that the antioxidant activity of suji extract of is classified as moderate as the IC50 value of the extract of suji is108,65 ppm